2015
DOI: 10.1177/0898010115570363
|View full text |Cite
|
Sign up to set email alerts
|

Meditation Interventions for Chronic Disease Populations

Abstract: The rapidly growing body of research regarding the use of meditation interventions in chronic disease presents an opportunity to compare outcomes based on intervention content. For this review, meditation interventions were described as those interventions delivered to persons with chronic disease where sitting meditation was the main or only content of the intervention with or without the addition of mindful movement. This systematic review identified 45 individual research studies that examined meditations e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(22 citation statements)
references
References 65 publications
1
18
0
3
Order By: Relevance
“…We found in the literature two meta-analyses on different meditation techniques for both symptoms. Both studies showed positive effects, with the strongest evidence for anxiety (Abbott et al 2014 ; Chan & Larson, 2015 ). However, none of the authors mentioned religious/spiritual meditation focus, which makes difficult the comparison with our study.…”
Section: Discussionmentioning
confidence: 99%
“…We found in the literature two meta-analyses on different meditation techniques for both symptoms. Both studies showed positive effects, with the strongest evidence for anxiety (Abbott et al 2014 ; Chan & Larson, 2015 ). However, none of the authors mentioned religious/spiritual meditation focus, which makes difficult the comparison with our study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, studies have shown that meditation may be a useful adjunct to the treatment of mental health problems, particularly mood and anxiety disorders234. Evidence also suggests benefits of meditation for people suffering from physical conditions, including hypertension5, insomnia6, irritable bowel syndrome7 and symptoms related to epilepsy, premenstrual syndrome and menopause2.…”
mentioning
confidence: 99%
“… 22 Another study reported that patients who were of an older age, female, better educated, and from upper-middle class families were more likely to use meditation. 42 The reason that we did not find that SES factors predicted the use of MSM in this study might be due to small sample size, or simply that certain symptoms played more important roles than SES factors in predicting use of MSM in these Chinese American women.…”
Section: Discussionmentioning
confidence: 60%